Maternal Perception and Attitudes Regarding Healthcare Professionals' Guidelines on Feeding Practices in the Child's First Year of Life - Mônica C. Broilo; Maria Laura C. Louzada; Maria de Lourdes Drachler; Lucia M. Stenzel; Márcia R. Vitolo (Brazilian Society of Pediatrics, 2013)
Objective: To evaluate the maternal perceptions and attitudes related to adherence to healthcare professionals' guidelines on breastfeeding and complementary feeding, and associated factors. Methods: A cross-sectional analysis of data from a randomized field trial was performed, in which 20 health centers (HCs) were selected in the city of Porto Alegre, state of Rio Grande do Sul, from eight Health Management Districts of the city. Pregnant women were selected from these HCs, and when the children were aged between six and nine months, data regarding the maternal perception of adherence to professional advice and consequences of feeding practices on child health were obtained during home visits. Association analyses were performed using Poisson regression. Results: Data were collected from 631 mother-child binomials. According to the mothers' perception, 47% reported not following instructions received in the HC. Among these, 45.7% did not recognize the importance of eating habits for the child's health. The perception of adherence to professional advice was associated with higher prevalence of exclusive breastfeeding (EBF), introduction of solid food (ISF) after four months, introduction of non-recommended foods after six months, and higher family income. A higher prevalence of EBF and ISF was observed after four months (p < 0.05) among mothers who believed in the importance of feeding habits for the child's health. Conclusion: There was a high prevalence of mothers who did not follow the advice of health professionals; the perception that food does not affect the child's health can be a barrier to the improvement of eating habits in childhood.